Methods of teaching the theoretical foundations of chemistry on the basis of problem-based learning (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article mainly presents the basics of the methodology of independent learning in the development of students ' independent thinking in the teaching of the theory of chemistry